Initial conditions and regional performance in the aftermath of disruptive shocks: The case of East Germany after socialism - Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena, 2020)
We investigate how initial conditions that existed in East Germany at the end of the socialist regime impact regional development during the turbulent shock transition to a market economic system. Our investigation spans a period of almost 30 years. Both the self-employment rate (an indication of the existence of a pre-socialist entrepreneurial tradition) and the share of the workforce with a tertiary degree have a strong positive effect on regional development. We conclude that knowledge and a tradition of entrepreneurship have long-run positive effects on development in regions that face disruptive shocks. Entrepreneurship and knowledge play a less important role for development across West German regions, where no significant shocks occurred.
Keywords: L26; R11; N93; N94; 330; Entrepreneurship; knowledge; economic development; history; transformation; East Germany